ANALISIS EFEKTIFITAS PROGRAM NASIONAL PEMBERDAYAAN MASYARAKAT DENGAN PINJAMAN MODAL USAHA (Studi Kasus Penerima Pinjaman Pada Desa Torongrejo, Kecamatan Junrejo, Kota Batu) - Saddam Krisiandry Putra; Supar tono (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2014)
This study aimed to determine the effect on the Business Capital Loan improve household incomes in the loan recipient Torongrejo as well as to determine the effectiveness of the program on poverty alleviation through income communities seen after receiving the loan with the level of poverty line. The data used are primary and secondary data obtained from the Central Statistics Agency (BPS) and the Village Office Torongrejo and Related Institutions supported by an interview to Business Capital Loan recipients. Based on information from the Central Bureau of Statistics poverty in its annual Batu not show a significant reduction rate, this is an important consideration given the level of poverty line continues to increase each him. In this study, there are two research focus is the increase in income after receiving the loan and the effectiveness of the program on poverty alleviation. Business Capital Loan programs are proven to increase the income of the recipient community but this loan program is less effective in reducing poverty on loan offenders, the proof is carried out with Wilcoxon test and the comparison of income levels with the level of poverty line. Keywords: Analysis, Effectiveness, Program for Community Empowerment, Business Capital Loan